2011
DOI: 10.1590/s0004-27492011000300003
|View full text |Cite
|
Sign up to set email alerts
|

Catarata pediátrica en un país en vías de desarrollo: revisión retrospectiva de 328 casos

Abstract: INTRODUCCIÓNLa catarata (Figura 1) se define como una opacidad del cristalino. En la edad pediátrica constituye una causa importante de disminución de la agudeza visual. En la actualidad se estima una incidencia de 1 a 13.6 por 10,000 nacimientos (1)(2)(3)(4) . En países en desarrollo la tasa de ceguera puede ser tan alta como 1.5 por 1000 habitantes, y la relacionada a la catarata pediátrica representa un enorme problema con relación a morbilidad, pérdida económica y aislamiento social (5) . Debido a la expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…While almost equal prevalence is reported for unilateral 48.8% (160/328) and bilateral cataracts 51.2% (168/328) from Guatemala City, Republic of Guatemala for the period from 2000 to 2007 by Zimmermann-Paiz & Quiroga-Reyes. 14 Higher prevalence of unilateral cataracts in our study can be explained by the fact that 20 out of 47 cases were traumatic in origin and traumatic cases are almost always unilateral.…”
Section: Descriptive Statistics and Estimation Of Parametermentioning
confidence: 52%
See 1 more Smart Citation
“…While almost equal prevalence is reported for unilateral 48.8% (160/328) and bilateral cataracts 51.2% (168/328) from Guatemala City, Republic of Guatemala for the period from 2000 to 2007 by Zimmermann-Paiz & Quiroga-Reyes. 14 Higher prevalence of unilateral cataracts in our study can be explained by the fact that 20 out of 47 cases were traumatic in origin and traumatic cases are almost always unilateral.…”
Section: Descriptive Statistics and Estimation Of Parametermentioning
confidence: 52%
“…The following authors have reported higher prevalence for unilateral than bilateral pediatric cataracts. 14 In a study for the period from 1985-1990, by Hochstrasser, et al 15 from Zürich, Switzerland, congenital/ developmental cataracts were found in 60% (45/75) cases while traumatic cataracts were found in 40% (30/75) cases. Johar, et al 16 Assuming 30% population of children, our reference population will be approximately 450,000.…”
mentioning
confidence: 99%
“…A retrospective review performed in Guatemala in 2011 of 328 cases of congenital (44.2%) and acquired (55.8%) cataracts in children 0-14 years of age found that the mean age of diagnosis for congenital cataract was 34.9 months, and treatment was not pursued in 71% of these cases. 53 There are no red reflex screening programs for newborns. Pediatric cataract surgeries are performed by ophthalmologists trained in pediatric surgery at hospital referral centers or by physicians volunteering for private organizations providing mobile eye services to underserved populations in Central America.…”
Section: Results: Regional Challengesmentioning
confidence: 99%
“…En los pacientes con seguimiento a 3 años, la única complicación observada en nuestra serie fue glaucoma (2 pacientes), siendo esta incidencia menor a lo reportado previamente (17-58,7%) 17,24,26 . Dado que fue realizada una capsulotomia posterior y vitrectomía anterior como parte de la técnica quirúrgica, no se observó opacidad de cápsula posterior como complicación, a diferencia de otros estudios que reportan una incidencia del 30,9% 26 .…”
Section: Discussionunclassified